Scientific medicine and public health in nineteenth-century latin america (2006)
Medical concepts and clinical attitudes characteristic of the Enlightenment- called 'proto-clinical' by Michel Foucault-changed signifiMedical concepts and clinical attitudes characteristic of the Enlightenment- called 'proto-clinical' by Michel Foucault-changed signifi cantly in postrevolutionary France during the late eighteenth century and the beginning of the nineteenth.1 Inside the modernizing trends of Renaissance and baroque medicine, such as iatrochemistry, iatromechanics, and vitalism, and nosologic botany-oriented systems,2 the medical system proposed by Hermann Boerhaave stands out for its hegemonic position. This system, nurtured as it was by earlier medical developments, integrated elements from the basic sciences of the time (anatomy, modern physics, and a chemistry free from iatrochemical interpretations) with pathology based on clinical observation, just as Thomas Sydenham had proposed several years earlier. Boerhaave founded in Leyden one of the most prestigious medical schools in Enlightenment Europe, and from there his disciples spread his theories throughout the continent.3 In spite of this, the multitude of classifi cations of illness and an inability to completely overcome Hippocratic and Galenic humoral pathology continued to characterize Enlightenment medicine, which maintained the elitist and aristocratic character inherited from medieval times. New political, social, and economic structures brought about by the French Revolution, however, created the conditions for a decisive rupture within the medical tradition of the ancien régime.4 It closed the hospitals and medical schools, which were considered the ramparts of the old model.5 In March 1791, in the name of individual liberty, the Legislature decreed that everyone was to be allowed the free exercise of any trade, including medicine. On August 18, 1792, that same body did away with universities and other academic centers.6 This created a crisis in public health.7 This crisis ended in 1794, when, on a totally different basis, new medical schools and hospitals were opened.8 A new course was embarked on that imposed practical instruction and turned hospitals into the center of medical life; teaching simultaneous with medical attention in hospitals overturned the almost artisanal, dominant forms typical of instruction in the medical schools of the ancien régime. © 2006 by the University of Texas Press. All rights reserved. cantly in postrevolutionary France during the late eighteenth century and the beginning of the nineteenth.1 Inside the modernizing trends of Renaissance and baroque medicine, such as iatrochemistry, iatromechanics, and vitalism, and nosologic botany-oriented systems,2 the medical system proposed by Hermann Boerhaave stands out for its hegemonic position. This system, nurtured as it was by earlier medical developments, integrated elements from the basic sciences of the time (anatomy, modern physics, and a chemistry free from iatrochemical interpretations) with pathology based on clinical observation, just as Thomas Sydenham had proposed several years earlier. Boerhaave founded in Leyden one of the most prestigious medical schools in Enlightenment Europe, and from there his disciples spread his theories throughout the continent.3 In spite of this, the multitude of classifi cations of illness and an inability to completely overcome Hippocratic and Galenic humoral pathology continued to characterize Enlightenment medicine, which maintained the elitist and aristocratic character inherited from medieval times. New political, social, and economic structures brought about by the French Revolution, however, created the conditions for a decisive rupture within the medical tradition of the ancien régime.4 It closed the hospitals and medical schools, which were considered the ramparts of the old model.5 In March 1791, in the name of individual liberty, the Legislature decreed that everyone was to be allowed the free exercise of any trade, including medicine. On August 18, 1792, that same body did away with universities and other academic centers.6 This created a crisis in public health.7 This crisis ended in 1794, when, on a totally different basis, new medical schools and hospitals were opened.8 A new course was embarked on that imposed practical instruction and turned hospitals into the center of medical life; teaching simultaneous with medical attention in hospitals overturned the almost artisanal, dominant forms typical of instruction in the medical schools of the ancien régime. © 2006 by the University of Texas Press. All rights reserved